Strategi Efektif Pembelajaran Khaligrafi dalam Menumbuhkan Kreativitas dan Kecintaan Terhadap Al-Quran di Pondok Pesantren Daarul Hikmah Asahan - Siddik, Ahmad Nur; Siregar, Bahtiar; Tumiran (Islamic Education, 2026)
This study aims to analyze calligraphy learning strategies in fostering students’ creativity and strengthening their love for the Qur'an at Daarul Hikmah Islamic Boarding School. This research is important because studies specifically examining the integration of calligraphy learning with the development of creativity and students’ emotional attachment to the Qur'an in Islamic boarding schools remain limited. This study employed a qualitative approach using a field research method. Data were collected through observations, interviews with the principal, calligraphy teachers, and students, as well as documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that the calligraphy learning strategy was implemented through three main stages: planning, implementation, and evaluation. In the planning stage, teachers prepared the curriculum, annual programs, weekly programs, and syllabus adapted to the boarding school context. In the implementation stage, teachers applied demonstration methods combined with lectures, direct practice, projector-based learning media, and assistance from teaching assistants to support students’ understanding. The evaluation stage was conducted through daily assessments, weekly tests, and final examinations for each khat style. The findings also show improvements in students’ creativity, particularly in originality of design, neatness of writing, accuracy of letter structure, and students’ confidence in producing calligraphic works. In addition, students demonstrated increased enthusiasm for reading, memorizing, and appreciating verses of the Qur'an through calligraphy activities. These findings imply that structured calligraphy learning can contribute to the development of artistic skills and support Qur'anic appreciation among students in Islamic boarding schools.